Cell cycle–regulated phosphorylation of p220(NPAT) by cyclin E/Cdk2 in Cajal bodies promotes histone gene transcription - Ma, Tianlin (Cold Spring Harbor Laboratory Press, 2000)
Cyclin E/Cdk2 acts at the G1/S-phase transition to promote the E2F transcriptional program and the initiation of DNA synthesis. To explore further how cyclin E/Cdk2 controls S-phase events, we examined the subcellular localization of the cyclin E/Cdk2 interacting protein p220(NPAT) and its regulation by phosphorylation. p220 is localized to discrete nuclear foci. Diploid fibroblasts in Go and G1 contain two p220 foci, whereas S- and G2-phase cells contain primarily four p220 foci. Cells in metaphase and telophase have no detectable focus. p220 foci contain cyclin E and are coincident with Cajal bodies (CBs), subnuclear organelles that associate with histone gene clusters on chromosomes 1 and 6. Interestingly, p220 foci associate with chromosome 6 throughout the cell cycle and with chromosome 1 during S phase. Five cyclin E/Cdk2 phosphorylation sites in p220 were identified. Phospho-specific antibodies against two of these sites react with p220 within CBs in a cell cycle–specific manner. The timing of p220 phosphorylation correlates with the appearance of cyclin E in CBs at the G1/S boundary, and this phosphorylation is maintained until prophase. Expression of p220 activates transcription of the histone H2B promoter. Importantly, mutation of Cdk2 phosphorylation sites to alanine abrogates the ability of p220 to activate the histone H2B promoter. Collectively, these results strongly suggest that p220(NPAT) links cyclical cyclin E/Cdk2 kinase activity to replication-dependent histone gene transcription.